(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Industrialisation is a significant aspect in the growth of developing as well as developed countries. Growth of countries around the globe is not possible without industries. Past studies on groundwater, surface waters and soils reveal the presence of pollutants especially the heavy metals. These contaminants are translocated through the roots of plants to the other parts of plants also such as leaves, fruits and grains. Human as well as natural activities both contribute heavy metals into the soil. Number of studies on variation of heavy metals in soil depth wise are very less. Therefore the present study is carried out to analyse heavy metals in agricultural land at different depths and to find correlation between them. Heavy metals such as Zn, Pb, Cd, Cu, As, Fe, Cr III and Ni are analysed as per standards of APHA and IS. Mean concentration of organic carbon and the studied heavy metals (total Zn, Total Pb, Total Cu, Fe, Ni) is found to get decreased with depth. Mean concentration of Cd and Cr III increases with depth. With depth mean value of pH increases i.e. on the whole soil becomes more alkaline with depth.